Effect of despotic leadership on organizational cynicism: role of moral disengagement and organizational identification - Ahtisham, Mirza Muhammad; Anwar ul Haq, Muhammad; Ahmed, Mirza Ashfaq; Khalid, Shaista (Business: Theory and Practice, 2023)
The purpose of this study was to find out the effect of despotic leadership on organizational cynicism both directly and with the mediating role of moral disengagement. It was also posited that organizational identification inversely moderates the effect of despotic leadership on organizational cynicism. Data was collected from the SMEs in Gujranwala Division of Punjab, Pakistan. The sample consisted of 280 randomly chosen front line employees from nine strata of SME manufacturing concerns. To empirically test the hypothesized model, SEM (Structural equation modelling) and Process Macros in SPSS 25 were used. The results confirm the hypothesized model. Despotic leadership has positive effect on organizational cynicism. Moral disengagement mediated between despotic leadership and organizational cynicism. Furthermore, results proved that employees higher on organizational identification were lesser cynic and vice versa. The study is first of its first kind and has advanced our understanding of dark leadership, cynicism, disengagement and organizational identification in the SMEs. The results guide the leadership practice by highlighting the ill-effects of despotic leadership. The study has important implications for literature, policy and managerial practice presented in the end.